Comparative study of heirloom tomato varieties - Oláh, J.; Ledóné Darázsi, H.; Dudás, L.; Krecz, Á.; Parragh, D.; Hodossi, S.; Fári, M. (International Journal of Horticultural Science, 2007)
The study examined the health status, growth type, berry morphology, berry quality, and gastronomical value of 60 heirloom tomato lines. In the middle of June, the level of virus infection was medium in the plant stock according to the assessments. 21% of the lines did not show symptoms of virus infection. During the vegetation period, the major fungal diseases were Alternaria by the middle of August and Phytophthora from the beginning of September. In spite of the fact that no fungicides were applied, 13% of the lines were healthy and 36% showed medium infection at the end of August. Half of the lines had a strong, 23% of the lines had a medium growth vigour. The majority (74%) of the lines showed strong or medium lateral shoot growth and only 7% of them proved to be less prone to branching. In spite of the rapid growth, 20% of the lines had a weak main stem, the majority of the lines had a main stem medium strength. The different shapes occurred in different colours, in addition to the traditional red colour (53%), there were orange, yellow, wine-red (blackish), lilac, green, almost white or multicoloured varieties. Unfortunately, most of the lines were prone to longitudinal or circular cracking of the berries. Based on the first experiences, all tested variety types had more favourable utilization characteristics then the traditional tomatoes. Varieties with a thick flesh and harmonic acid/sugar ratio such as some of the ox-heart varieties are especially valuable. For drying, the elongated types proved to be the best. The hollow tomato is the most special type which can be utilized most diversely. It is especially suitable for making white tomato soup and, “Concasse" due to its easily removable placenta rich in jelly materials and its thick flesh. In addition, it can be used for preparing stuffed tomato.